Study of changes in land cover categories in Ukraine based on remote sensing data - Ren, L. (Land Management, Cadastre and Land Monitoring, 2023)
Land cover change has been a hot area of research on global ecological change and sustainable development due to its importance in global ecological change. Understanding land cover change trends is the basis for rational planning and management of land resources and is of important value for achieving land protection and sustainable development. Land transfer matrix has great value in the research of land cover change, its results are not disturbed by the land cover category and quantity, and the data can be analyzed in different time periods according to the demand. However, the land transfer matrix produced by traditional methods has the problems of long production period and certain requirements for hardware performance. In this paper uses Google Earth Engine to obtain the public land cover dataset of Ukraine and uses raster calculation to quickly construct the land transfer matrix. The matrix data show that the land cover change in Ukraine from 2000-2015 is modest, with a total change of 2.244%. The proportion of cropland decreased and the proportion of Urban and Built-up Lands increased. The results show that the methods can quickly and effectively obtain data on land cover change in the study area and provide assistance in analyzing trends and patterns of land cover change.Keywords: Land cover change, Google Earth Engine, land transfer matrix
Keywords: Land cover change; Google Earth Engine; land transfer matrix.